PRODUCTION OF FRUITS IN INDIA - Ganesh Datt Bhatt, Pallavi Tyagi (International Journal of Modern Agriculture, 2021)
India has diversity in soil & climate for agriculture and horticulture crop providing plenty chances for the advancement of fruit-industry. The biggest challenge in the present is- to produce sufficient fruits to feed the growing population. Fruit is very essential to human-beings & plays a significant role in spiritual performs, tradition & art. Fruits are delicious and have many of the nutrients which are necessary for the human-health. India is 2nd major grower of fruit in the whole world. The study is based on the production of fruits and its associated challenges and issues in the country. The production of fruits is very important and needful to every human and in demand that also greatly helpful in the development of Indian economy. The production of fruits is largest in the three main state of India: H.P(Himachal Pradesh), Jammu & Kashmir (J&K) & in Uttar-Pradesh (U.P.). India's massive agricultural resources alone makes huge prospective for investments in its fruit processing and equipment industry. Major areas holding scope for valuable processing are in the canning, dairy, packaging and food processing and thermo-processing industries. Fruit crops are concerned heavyweight expenditure on research, development and regulatory approval and market hurdles limit the profitable application of Biotechnology. The development of new technologies is future strategy to solve the problems of hunger, poverty, malnutrition and the diseases in the economically developing countries and underdeveloped nation